The impact of agricultural intensification on bee health and abundance - Pérez Lagleyze, Ignacio (2025)
Bee populations are declining due to agricultural expansion, habitat loss, and diseases such as nosemosis caused by microsporidian Vairimorpha spp. We evaluate how agricultural intensification affects the abundance of wild (Augochloropsis spp.) and managed (Apis mellifera) bees and how landscape modification impacts bee health quality by altering their susceptibility to be infected by Vairimorpha spp. Bees were collected using pan traps in nine fields with varying management intensities from Argentina, while landscape management intensity was assessed using satellite imagery for each field. We found the abundance of one wild bee species increases as the proportion of landscapes with low intensity management increases. Vairimorpha spores were only found in managed bees. We also found that prevalence of Vairimorpha increases as the proportion of intensive management increases. Our results suggest that agricultural intensification negatively impacts the abundance of wild bee populations and makes managed bees more susceptible to Vairimorpha spp. infection.